Talent identification in youth basketball: Talent scouts´ perceptions of the key attributes for athlete development - Larkin, P.; Sanford, M.; Talpey, S.; Gorman, A. D.; Reeves, M. J. (International Sport Coaching Journal, 2022)
The objective of this study is to understand the attributes youth coaches and talent scouts perceive as important when identifying skilled youth basketball players. Youth coaches and talent scouts (n = 40) from Australia, Canada, the United Kingdom, and United States with an average of 14.09 (±9.77) years of experience completed an online questionnaire. The questionnaire asked participants to rank and justify attributes for identifying potentially talented youth basketball players according to their perceived importance. In addition, five youth coaches and talent scouts completed a semistructured interview that elaborated on how they identify these attributes in national-level youth players. Results from the questionnaire indicate a hierarchy of attributes coaches/scouts perceive as important for youth basketball performance, including tactical (i.e., decision-making ability), technical (i.e., layup, shooting in the paint, jump shot, rebounding), and psychological attributes (i.e., composure, concentration, adaptability). In addition, the results from the interviews provided more detailed justification for the importance of these attributes within the talent identification process. It is believed talent scouts apply a holistic multidisciplinary approach to talent identification, with the current findings potentially providing evidence to suggest coaches/scouts consider a wide range of tactical, technical, psychological, and physical attributes when identifying youth players.